2013
DOI: 10.1002/mnfr.201200794
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol ameliorates atherosclerotic plaque formation, hypercholesterolemia, and hepatic steatosis in ApoE‐deficient mice

Abstract: Scope: Xanthohumol (XN), a prenylated antioxidative and anti-inflammatory chalcone from hops, exhibits positive effects on lipid and glucose metabolism. Based on its favorable biological properties, we investigated whether XN attenuates atherosclerosis in western-type diet-fed apolipoprotein-E-deficient (ApoE −/− ) mice. Methods and results: XN supplementation markedly reduced plasma cholesterol concentrations, decreased atherosclerotic lesion area, and attenuated plasma concentrations of the proinflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 51 publications
2
44
1
Order By: Relevance
“…The anti-obesity effect of XN in mouse models might be explained by reduced SREBP1c mRNA expression [12], by decreased de novo lipogenesis through the inhibition of SREBP maturation in the mouse liver [29], and by reduced mRNA expression of hepatic genes involved in fatty acid synthesis and gluconeogenesis [14]. The decreased production of mature SREBPs was also demonstrated in cell culture studies using Huh-7 (a human hepatoma cell line) cells [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-obesity effect of XN in mouse models might be explained by reduced SREBP1c mRNA expression [12], by decreased de novo lipogenesis through the inhibition of SREBP maturation in the mouse liver [29], and by reduced mRNA expression of hepatic genes involved in fatty acid synthesis and gluconeogenesis [14]. The decreased production of mature SREBPs was also demonstrated in cell culture studies using Huh-7 (a human hepatoma cell line) cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…In a diet-induced animal model of non-alcoholic steatohepatitis, daily oral administration of XN at a dose level of approximately 1000 mg/kg body weight exhibited anti-inflammatory and anti-fibrogenic effects [9]. In ApoE −/− mice fed diets containing XN (300 mg/kg body weight/day) for 8 weeks, there was a decrease in hepatic triglyceride and cholesterol content accompanied by the activation of AMP-activated protein kinase, phosphorylation and inactivation of acetyl-CoA carboxylase, and reduced expression of hepatic sterol regulatory element-binding protein (SREBP) 1c mRNA [12]. In genetically obese KK-A y mice, XN lowered fasting plasma glucose, plasma and hepatic triglyceride concentrations, and weights of white adipose tissue [14].…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is characterized by a dysfunction of hepatic lipid metabolism [28,29]. In order to investigate the possible mechanisms regarding the observed differences in serum and liver lipid levels, we quantified mRNA expression levels of key liver enzymes in fatty acid and triglyceride synthesis and cholesterol efflux.…”
Section: Resultsmentioning
confidence: 99%
“…Peroxidative changes that take place during liver injury as well as hypercholesterolemia have responded positively with selective inhibition of COX-2 (15). ApoE-deficient mice show similar response to xanthohumol, a prenylated chalconoid with antiinflammatory activities (16). Lowering the levels of LDL-cholesterol is one of the keystones in the prevention of cardiovascular disease and statins are the drug of choice to achieve the goal, but unfortunately it was reported that even at the highest dose of administration only limited additional lowering may be attained with increased incidence of side effects (17).…”
Section: Discussionmentioning
confidence: 99%
“…Each morning at selected time points, i.e. at weeks 0, 2,4,6,8,10,12,14,16,18, and 20, blood was withdrawn from the marginal ear vein of the rabbits and tests were done within 2-3 h. Ethical approval of the study was obtained from the Kohat University of Science and Technology (AERC01092011). All the tested animals were treated in conformity with the highest ethical guidelines of the National Institutes of Health (USA).…”
Section: Methodsmentioning
confidence: 99%